The Effects Of The Museums’ Circulation Design On The Elderly Visitors’ Satisfaction In Peninsular Malaysia - Elottol, Raed M. A. (2011)
The study examines how elderly visitors‘ expectations, interior circulation design quality, and satisfaction are related in the context of interior design of museums. This study explores a theoretical as well as practical key issue in interior circulation design in museums in Peninsular Malaysia. The research intends to investigate the interior circulation design that interacts with the interior environment and space planning in museums. This is to fully understand the relationship between elderly visitors‘ satisfaction and interior circulation design.